A study on the essential oil of Wedelia biflora (L) D.C. (Fam. Compositae) - Curaming, Rodrigo Carrion; Castillo, Amorita V.; Concepcion. Adoracion B. (Quezon City: College of Pharmacy, University of the Philippines, 1979.)
The fresh leaves of Wedelia biflora (Linn.) DC. (Fam. Compositae) yielded approximately from 0.71% to 0.76% essential oil. Its moisture content was 83.4%. The oil gave a refreactice index (28°C) of 1.5989. the oil has an aromatic odor and slightly sweetish in taste. When freshly distilled, it is colorless, turning yellow on standing.
Thin layer chromatography has manifested that the oil is very soluble in ethyl alcohol, slightly soluble in chloroform and in diethylamine, and insoluble in benzene.
Ultraviolet spectrophotometry revealed that the oil has a single component and absorbed a wavelength of 222 nm.
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, 1979.
Keywords: Compositae; Hagonoi; Hagonoi-tsina.